The palaeoenvironmental potential of bioarchaeological isotope data - Depaermentier, Margaux L C; Kempf, Michael; Vander Linden, Marc; Britton, Kate; Madgwick, Richard; Büntgen, Ulf; Drucker, Dorothée G; Jones, Jennifer R; Snoeck, Christophe; Stevens, Rhiannon E (Communications earth & environment, 2025)
Bioarchaeology not only provides insights into human, animal, and environmental ecology, but also generates huge amounts of stable and radiogenic isotope data that are not well recognised by other disciplines. Here, we present potential avenues for the integration and interpretation of archaeological isotope data into environmental studies. We emphasise the large spatio-temporal scales on which isotope patterns can be observed, for example using isoscapes, the limitations and potential pitfalls that come with isotope data from archaeological research, and future cross-disciplinary collaborations between bioarchaeology and other palaeo-disciplines.
Keywords: Geochemistry; Element cycles; Environmental monitoring